2003
DOI: 10.1074/jbc.m212635200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Phosphorylation of Glycogen Synthase Kinase-3 (GSK-3) in Response to Lithium

Abstract: Glycogen synthase kinase-3 (GSK-3) is a critical, negative regulator of diverse signaling pathways. Lithium is a direct inhibitor of GSK-3 and has been widely used to test the putative role of GSK-3 in multiple settings. However, lithium also inhibits other targets, including inositol monophosphatase and structurally related phosphomonoesterases, and thus additional approaches are needed to attribute a given biological effect of lithium to a specific target. For example, lithium is known to increase the inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
329
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 407 publications
(352 citation statements)
references
References 90 publications
13
329
0
3
Order By: Relevance
“…Initially, Zhang et al [46] reported the existence of an autoregulatory loop whereby GSK3 regulates its own phosphorylation at Ser21/9. In this case, the phosphorylation and inhibition of I-2 by GSK3 results in increased PP1 activity and decreased Ser21/9 phosphorylation of GSK3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, Zhang et al [46] reported the existence of an autoregulatory loop whereby GSK3 regulates its own phosphorylation at Ser21/9. In this case, the phosphorylation and inhibition of I-2 by GSK3 results in increased PP1 activity and decreased Ser21/9 phosphorylation of GSK3.…”
Section: Resultsmentioning
confidence: 99%
“…The regulation of Ser21/9 phosphorylation has been attributed to the actions of protein phosphatase-2A (PP2A) [40,43,27,38] and protein phosphatase-1 (PP1) [46,34,41]. The PP1 holoenzyme is comprised of a 37 kDa catalytic subunit which associates with inhibitory subunits and targeting subunits.…”
Section: Introductionmentioning
confidence: 99%
“…The observed reduced level of p-GSK3b, thus higher GSK3b activity in bipolar fibroblasts, may also underlie the rationale for lithium treatment of bipolar disorder since lithium directly inhibits GSK3b resulting in N-terminal phosphorylation of GSK3b at serine 9. 61 It was reported that the level of p-GSK3b in peripheral blood mononuclear cells from subjects with bipolar disorder under lithium treatment is significantly higher than that in healthy control subjects, 100 although no difference was detected between lithium-free bipolar and healthy controls. We postulate that the genetically heterogeneous nature of the samples may account for the failure of detecting p-GSK3b level difference between lithiumfree bipolar and healthy controls, as we encountered when including samples from members of non-Amish family 884 in our analysis.…”
Section: Discussionmentioning
confidence: 98%
“…Among these kinases, GSK3b is of particular interest here because it was reported to be one of the direct targets of lithium, 60 which is an effective therapy for bipolar disorder. 22,23 The activity of GSK3b can be inhibited by lithium, 60 which results in the phosphorylation of GSK3b at Ser9, 61 and the level of p-GSK3b indicates the activity of GSK3b. 28 Similar to the circadian pacemaker in the SCN in mammals, cultured cells, including fibroblasts, harbor self-sustained and cell-autonomous circadian clocks that persist even during cell division.…”
Section: Introductionmentioning
confidence: 99%
“…We further transfected the SKOV3 cells with GID5-6, a peptide inhibitor of GSK-3β derived from the GSK-3β interaction domain of axin [20]. The control GID5-6LP contains a single amino acid mutation rendering it unable to interact with GSK-3β [20,21]. Transfection with GID5-6 led to decrease of BrdU intake in SKOV3 cells (20% positive), compared with cells transfected with GID5-6LP (32.4% positive).…”
Section: Gsk-3β Activity Modulated Skov3 Cell Proliferationmentioning
confidence: 99%